Antiproliferative activity of cycloalkanecarboxamide derivatives possessing sulfonate or sulfamate moiety - El-Gamal, Mohammed, I; Omar, Hany A.; Semreen, Mohammad H.; Younes, Israa A.; Zaghloul, Youmna Y.; Abbas, Ayat E.; Moussa, Iman G.; Hersi, Fatima; Oh, Chang-Hyun (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
A series of cycloalkanecarboxamide-containing sulfonate and sulfamate derivatives were prepared, and their antiproliferative activity was tested against NCI-60 cancer cell lines panel. Compound if possessing cyclohexyl and p-(tert-butyl)benzenesulfonate moieties was the most active among all the target compounds. It exerted broad-spectrum anticancer activity against all the nine cancer types involved in the NCI-60 panel. Additionally, compound 1g containing cyclohexyl and p-fluorobenzenesulfonate moieties was the most potent against HT29 colon cancer cell line (IC50 = 4.73 mu M) with selectivity index more than 4.23 towards HT29 than normal fibroblasts. It exerts its antiproliferative activity against HT29 through the induction of apoptosis (increasing caspase 3/7 activity) but not necrosis. Structure-activity relationship studies are presented in detail.